PEMBUATAN TEPUNG MOKAL DENGAN PENAMBAHAN BIANG FERMENTASI ALAMI UNTUK BERAS ANALOG - Sri Budi Wahjuningsih (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
One of the problems of food diversification in Indonesia, particularly the diversification of staple food is rice dependency. This was caused by a shift in the pattern of staple food in Indonesia are rice as a staple food made of single ( Ariani et al, 2010). On the other hand, Indonesia is rich source of carbohydrate products such as corn, sorghum, sago, cassava, and other root crops as well as a variety of plant protein sources such as green beans, Tolo beans, kidney beans, lentils sword, and soybeans. These materials have been used as food, but it still can not replace rice as a staple food. One of the non -carbohydrate sources of refined products similar to rice paddy developed lately is analogous artificial rice or rice. Rice analog can increase the diversification of staple foods without changing the eating habits of people. However, the constraints of analog rice flour by mocaf is no protein content. Therefore, this study aims to enrich the analog rice flour made from mocaf with various types of nuts as a protein source, ie mung bean flour, soy flour, red bean flour, Tolo beans flour, lentils and sword flour. The results of chemical analysis and organoleptic formulation obtained rice is the best analog in the treatment T1 (mocaf 75 % and 25 % red beans ) with a nutrient content : 4.21 % moisture, 2.08 % ash content, fat content of 0,19 %, 6,46% protein content, carbohydrate content of 87,07 %, 8,66 % dietary fiber, and a score of 4.32 ( really like ).